1996
DOI: 10.1111/j.1469-8137.1996.tb01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the parasitic angiosperm Orobanche aegyptiaca and its tomato host: growth and biomass allocation

Abstract: The influence of the parasitic angiosperm Orobanche aegyptiaca on the growth and shoot/root allometry of tomato plants was studied in two experiments. In the first, the density of infection was manipulated, with host and parasite biomass being measured 56 d after planting (d.a.p.). In the second, multiple harvests were made from 14 to 91 d.a.p. at one level of infection (20 mg seed dm""). The first experiment demonstrated an approximately linear reduction in host biomass up to 10 mg seed dm"^ soil, beyond whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
34
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 10 publications
(9 reference statements)
12
34
4
Order By: Relevance
“…the biomass of infected plants was lower than that of their uninfected counterparts, consistent with reports of other host : Orobanche associations (Zaitoun, Al-Menoufi & Weber, 1991 ;Barker et al, 1996 ;Hibbered et al, 1996Hibbered et al, , 1998. Initially (33 d.a.p.…”
Section: Responses Of Trifolium Repens To Infectionsupporting
confidence: 79%
See 1 more Smart Citation
“…the biomass of infected plants was lower than that of their uninfected counterparts, consistent with reports of other host : Orobanche associations (Zaitoun, Al-Menoufi & Weber, 1991 ;Barker et al, 1996 ;Hibbered et al, 1996Hibbered et al, , 1998. Initially (33 d.a.p.…”
Section: Responses Of Trifolium Repens To Infectionsupporting
confidence: 79%
“…), infected plants had greater calculated biomass than uninfected plants. Consistent with this observation, ter Borg (1986) and Barker et al (1996) reported a slight stimulation of relative growth rate of the host soon after infection with Orobanche, although such accounts are rare. The combined biomass of infected T. repens and O. minor (association biomass) was lower than that of control T. repens at ambient CO # .…”
Section: Responses Of Trifolium Repens To Infectionsupporting
confidence: 63%
“…However, unlike some other reports which showed a reduction of shoot biomass of the infected host (Barker et al, 1996; Mauromicale et al, 2008), total biomass of wild type plants in the present study was mainly reduced through a decrease in root biomass ( Figure 3 ). This may be due to the different tomato cultivars that were used, and/or the different growing conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…These results join those of Press, [53] and of Barker et al, [54] which underlines the reduction in the photosynthetic capacity and in the ratio aerial-parts DW / roots DW of tomato plants parasitized by the specie P. aegyptiaca. Such an impact seems to be a common response to the plants parasitized by the broomrape [55,56].…”
Section: Discussionsupporting
confidence: 79%